2017
DOI: 10.1016/j.expneurol.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial cristae remodelling is associated with disrupted OPA1 oligomerisation in the Huntington's disease R6/2 fragment model

Abstract: There is evidence of an imbalance of mitochondrial fission and fusion in patients with Huntington's disease (HD) and HD animal models. Fission and fusion are important for mitochondrial homeostasis including mitochondrial DNA (mtDNA) maintenance and may be relevant for the selective striatal mtDNA depletion that we observed in the R6/2 fragment HD mouse model. We aimed to investigate the fission/fusion balance and the integrity of the mitochondrial membrane system in cortex and striatum of end-stage R6/2 mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 56 publications
(42 reference statements)
5
23
0
Order By: Relevance
“…Previous study has recommended that mitochondrial fission could affect mitochondria‐related proteins oligomerization including OPA . In this study, our findings confirmed the above conclusion.…”
Section: Discussionsupporting
confidence: 91%
“…Previous study has recommended that mitochondrial fission could affect mitochondria‐related proteins oligomerization including OPA . In this study, our findings confirmed the above conclusion.…”
Section: Discussionsupporting
confidence: 91%
“…Images were exported to a tablet-PC (iPad2, Apple) and the mitochondrial area and number were evaluated using the Glow Draw application (The Othernet, LLC © Daniel Cota), followed by quantification using ImageJ software (ImageJ 1.46r, Wayne Rasband, National Institutes of Health, USA). The median of individual results from each of the five images was calculated for the mitochondrial area and number [34].…”
Section: Electron Microscopymentioning
confidence: 99%
“…mRNA isolation and quantitative real-time PCR mRNA was isolated with the RNeasyPlus Mini Kit (74134, Qiagen) and 2 µg of RNA was reverse-transcribed into cDNA with the iScript cDNA synthesis kit (Bio-Rad). Quantitative real-time PCR (qPCR) was performed using SYBR® green supermix with the CFX384 Touch Real-Time PCR Detection Systems (Bio-Rad) as previously described [28,34]. Primer…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The mediator for this event is identified as optic atrophy 1 factor (OPA1), a factor responsible in causing mitochondrial swelling and organelle rupture [51][52][53]. Other mPTP inhibitors such as CsA, BGK and Ru360, have been identified to reduce percentage of cristae cells [54,55]. The increased permeability of inner mitochondrial membrane allows for more protons, ions and solutes (up to 1.5 kDa in size) to pass through, consequently affecting the chemio-osmotic function of mitochondria [39,50].…”
Section: Iii) 'Ros-induced Ros Release' Phenomenon: Mitochondrial Trimentioning
confidence: 99%
“…Numerous reports have also linked TCTs with cell morphological features related to OS induced-apoptosis [55,80,81]. Human lung and brain cancer cell lines, for example, when treated with 3µM β-TCT for 24 h, showed nuclear chromatin condensation, equivalent to mid-apoptosis.…”
Section: Iv) Tocotrienols Trigger Major Apoptosis Pathway Involving Cmentioning
confidence: 99%